2019
DOI: 10.1002/jcp.28658
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic‐based therapy for colorectal cancer: Prospect and involved mechanisms

Abstract: Epigenetic modifications are heritable variations in gene expression not encoded by the DNA sequence. According to reports, a large number of studies have been performed to characterize epigenetic modification during normal development and also in cancer. Epigenetics can be regarded more widely to contain all of the changes in expression of genes that make by adjusted interactions between the regulatory portions of DNA or messenger RNAs that lead to indirect variation in the DNA sequence. In the last decade, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 234 publications
(355 reference statements)
0
22
0
Order By: Relevance
“…The discovery of the JAK/STAT pathway happened through a series of investigations looking into the relationship between interferon responses and signal transduction (Velazquez et al, 1992). The STAT family includes seven members: STAT1, STAT2, STAT3, STAT4, STAT5 (a/b), and STAT6 (Subramaniam et al, 2013;Rezapour et al, 2019). There is a standard structural pattern in all seven STAT proteins (Figure 1).…”
Section: Stat Signalingmentioning
confidence: 99%
“…The discovery of the JAK/STAT pathway happened through a series of investigations looking into the relationship between interferon responses and signal transduction (Velazquez et al, 1992). The STAT family includes seven members: STAT1, STAT2, STAT3, STAT4, STAT5 (a/b), and STAT6 (Subramaniam et al, 2013;Rezapour et al, 2019). There is a standard structural pattern in all seven STAT proteins (Figure 1).…”
Section: Stat Signalingmentioning
confidence: 99%
“…An inverse correlation was observed between the NKX2.2 methylation and its transcriptional levels. (2) No significant association was found between the NKX2.2 methylation and sex, age, tumor differentiation, TNM stage, CEA, CA199, and fecal occult blood.…”
Section: Discussionmentioning
confidence: 94%
“…DNA methylation was regarded to regulate the changes in expression of genes that make by adjusted interactions between DNA and messenger RNAs. In the past decades, methylation modification in CRC pathogenesis was demonstrated powerfully [2]. It was reported that NKX2.2 was dysregulated in a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On top of non-coding RNAs-based regulation of therapeutic resistance in CRC, epigenetic changes that involve DNA methylation and histone modifications have also increasingly been reported ( Shen et al, 2018 ; Mahalakshmi, Husayn Ahmed & Mahadevan, 2018 ; Porcellini et al, 2018 ; Rezapour et al, 2019 ). For instances, hypermethylation of genes such as MEIS2 , SLFN11 and B4GALT1 are associated with cancer progression and resistance to chemotherapy (cisplatin or oxaliplatin-based therapy) and anti-EGFR therapy ( Baharudin et al, 2017 ; He et al, 2017 ; Picardo et al, 2019 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%